Plasma lipids and coagulation in patients with arteriosclerotic dementia. Issue 9 (September 1974) - Andreoli, V. M.; Ferrari, S.; Sirtori, C. R.; Biasi, G.; Morandini, M.
Abstract : Plasma lipids and lipoproteins, glucose, uric acid, and haemocoagulative parameters were studied in a group of 22 elderly hospitalized patients with arteriosclerotic dementia, and compared with those of a control group of a similar age. No significant differences were found in lipids, lipoproteins, glucose, or uric acid but the fibrinogen level was significantly raised in the group with arteriosclerotic dementia. A comparison of the metabolic parameters of the dementia patients with those of a group of subjects with peripheral occlusive arteriosclerosis showed, on the other hand, that this latter group had significantly raised plasma triglycerides as well as a significantly higher incidence of the Fredrickson phenotypes of hyperlipoproteinaemia. These findings indicate that the common laboratory parameters used to evaluate arteriosclerosis are not adequate to point out any pathogenic mechanism for arteriosclerotic dementia, and research should therefore be focused in other directions.